2022
DOI: 10.1016/j.xjidi.2022.100095
|View full text |Cite
|
Sign up to set email alerts
|

Cannabinoids for the Treatment of Dermatologic Conditions

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 39 publications
0
30
0
Order By: Relevance
“…One study reported that the topical application of an emollient cream containing N-palmitoyl ethanolamine (PEA), a cannabinoid receptor CB2 agonist, reduced itch on average by 86.4% in patients with refractory, chronic pruritus of various etiologies [11,24] ; another open-label study evaluated PEA-containing cream in atopic dermatitis patients and reported decreased pruritus with a tolerance of 92% [25] . Since then, there have been several new formulations of topical cannabinoid oils for itch, including endocannabinoids such as anandamide, phytocannabinoids, and synthetic cannabinoids [26,27] . Xerosis is also reported to be reduced in 81% of patients [28] .…”
Section: Cannabinoidsmentioning
confidence: 99%
“…One study reported that the topical application of an emollient cream containing N-palmitoyl ethanolamine (PEA), a cannabinoid receptor CB2 agonist, reduced itch on average by 86.4% in patients with refractory, chronic pruritus of various etiologies [11,24] ; another open-label study evaluated PEA-containing cream in atopic dermatitis patients and reported decreased pruritus with a tolerance of 92% [25] . Since then, there have been several new formulations of topical cannabinoid oils for itch, including endocannabinoids such as anandamide, phytocannabinoids, and synthetic cannabinoids [26,27] . Xerosis is also reported to be reduced in 81% of patients [28] .…”
Section: Cannabinoidsmentioning
confidence: 99%
“…Structurally, THC and CBD are classical cannabinoids [71]. Phytocannabinoids and their receptors are summarized in Table 3.…”
Section: Phytocannabinoidsmentioning
confidence: 99%
“…15,16 The phytocannabinoid family includes over 100 compounds, among which delta-9-tetrahydrocannabinol [Δ 9 -THC] and cannabidiol [CBD] are the most notable. 16 16 Synthetic cannabinoids were first synthesized in the 20th century-dronabinol and nabilone are two prominent examples. 16 The FDA approved these two compounds for treating acquired immunodeficiency syndrome-induced anorexia and chemotherapy-induced nausea and vomiting.…”
Section: S E Arch S Tr Ategy and Me Thodmentioning
confidence: 99%
“…The phytocannabinoid family includes over 100 compounds, among which delta‐9‐tetrahydrocannabinol [Δ 9 ‐THC] and cannabidiol [CBD] are the most notable 16 . Anandamide [AEA], 2‐arachidonoylglycerol [2‐AG], and the endogenous fatty acid amide N‐palmitoylethanolamide [N‐PEA] are the three most important and clinically relevant endocannabinoids 16 . Synthetic cannabinoids were first synthesized in the 20th century—dronabinol and nabilone are two prominent examples 16 .…”
Section: Classification Of Cannabinoidsmentioning
confidence: 99%
See 1 more Smart Citation